10k-(2k-6)-(2k-3)=-4

Simple and best practice solution for 10k-(2k-6)-(2k-3)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10k-(2k-6)-(2k-3)=-4 equation:


Simplifying
10k + -1(2k + -6) + -1(2k + -3) = -4

Reorder the terms:
10k + -1(-6 + 2k) + -1(2k + -3) = -4
10k + (-6 * -1 + 2k * -1) + -1(2k + -3) = -4
10k + (6 + -2k) + -1(2k + -3) = -4

Reorder the terms:
10k + 6 + -2k + -1(-3 + 2k) = -4
10k + 6 + -2k + (-3 * -1 + 2k * -1) = -4
10k + 6 + -2k + (3 + -2k) = -4

Reorder the terms:
6 + 3 + 10k + -2k + -2k = -4

Combine like terms: 6 + 3 = 9
9 + 10k + -2k + -2k = -4

Combine like terms: 10k + -2k = 8k
9 + 8k + -2k = -4

Combine like terms: 8k + -2k = 6k
9 + 6k = -4

Solving
9 + 6k = -4

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 6k = -4 + -9

Combine like terms: 9 + -9 = 0
0 + 6k = -4 + -9
6k = -4 + -9

Combine like terms: -4 + -9 = -13
6k = -13

Divide each side by '6'.
k = -2.166666667

Simplifying
k = -2.166666667

See similar equations:

| 4x+3(2x+7)=81 | | -2x+10=-24 | | 2k+3(2k+2)=2(3k-1) | | 0=/9 | | 121=5+6(-4v+5) | | 8c-4=20 | | n=5-2+4 | | 8w+2x-6w+3w= | | -2(q-29)=-1/2(4-8q) | | 4y-12x=108 | | T+19=25 | | 4x-2(x-3)=-7+5x-8 | | -9x+-3=24 | | 7(n+7)=19+2n | | .3*300=x | | 0.03=6 | | 18(x-1)=12(x+3) | | 8x+10x=7 | | .3*300= | | 6(a+4)(a-7)=0 | | 7st+6su+8sv= | | X-6=7y | | 120=6x-6x | | 16x+4x=19+x | | n=5m+4 | | x+(x*.25)=183 | | (x^2+4x+4)(x^2-6x+9)=(-1) | | -3y-8=2y+17 | | (2x+39)+(x-7)+(x)=180 | | =4(a+9) | | (3r+8)(r-8)=0 | | log(x)=log(-2x+5) |

Equations solver categories